2020
DOI: 10.3390/cancers12082138
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle Transfer from Endothelial Cells Drives VE-Cadherin Expression in Breast Cancer Cells, Thereby Causing Heterotypic Cell Contacts

Abstract: Cadherins mediate cohesive contacts between isotypic cells by homophilic interaction and prevent contact between heterotypic cells. Breast cancer cells neighboring endothelial cells (ECs) atypically express vascular endothelial (VE)-cadherin. To understand this EC-induced VE-cadherin expression in breast cancer cells, MCF7 and MDA-MB-231 cells expressing different endogenous cadherins were co-cultured with ECs and analyzed for VE-cadherin at the transcriptional level and by confocal microscopy, flow cytometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…VE-cadherin belongs to the calcium-dependent adhesin family and is mainly expressed at the adhesion sites of endothelial cells. It plays an important role in endothelial cell migration and survival, angiogenesis, and maintenance of vascular integrity ( Rezaei et al, 2020 ). Studies have found that VE-cadherin enhances the VM ability of liver cancer cells ( Shuai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…VE-cadherin belongs to the calcium-dependent adhesin family and is mainly expressed at the adhesion sites of endothelial cells. It plays an important role in endothelial cell migration and survival, angiogenesis, and maintenance of vascular integrity ( Rezaei et al, 2020 ). Studies have found that VE-cadherin enhances the VM ability of liver cancer cells ( Shuai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[6,34] Moreover, the hydrogel is acting as a 3D microenvironment which can give essential stimuli to cultivated cells. [7] An additional advantage has been shown in the field of studying cell-cell interactions [4] as the co-encapsulation of cell types results in a close co-localization for studying their isolated interaction. Cell-laden hydrogel beads represent a porous and diffusable system that is ideal for implementing staining procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Microfluidic systems have been used in several eukaryotic cell culture applications such as analyzing tumor organoids, [1,2] cell-cell interactions, [3,4] single-cell immune dynamics, [5] and the analysis of stem cell behavior including differentiation studies [6,7] but also for the single-cell culture of prokaryotes. [8][9][10] Although these studies show the potential of microfluidics for cell culture applications, microfluidic procedures are still difficult to implement in biological laboratories without intensive investments into equipment and personal resources.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from liver cancer models also showed that anti-VEGR treatment triggered the release of VEGF-enriched exosomes that stimulate angiogenesis (Zeng et al, 2019). EVs can also activate VEGF-independent pathways such as those mediated by hepatocyte growth factor (HGF) to enable TKI-induced cell death (Qu et al, 2016). Exosomal miR-19b derived from cancer stem cells could promote angiogenesis (Wang et al, 2020).…”
Section: Exosomesmentioning
confidence: 99%
“…In human HCC HepG2 cells, Twist1 enhanced the cancer stem-like cell behaviors to adopt an EC-like phenotype, prompting cell motility, invasiveness, and VM formation ( Sun et al, 2010 ). VE-cadherin was transported by extracellular vehicles (EVs) from human umbilical vein endothelial cells (HUVECs) to breast cancer cells, which promotes the VM in a chicken chorioallantois membrane tumor model ( Rezaei et al, 2020 ).…”
Section: Angiogenesis In Tumormentioning
confidence: 99%